The Effect of Problem Based Learning Model and Differentiation Approach on the Results of Natural and Social Science Learning of Grade V Students - Leny Amalia; Ika Ratnaningrum (Postgraduate, University of Mataram, 2025)
This study examines the impact of the problem-based learning model and differentiated approach on the learning outcomes of natural and social science students in grade V at SD Mahesa Jenar Cluster, Ambarawa District, Semarang Regency. Interviews and observations revealed that students learning outcomes remain low due to monotonous, teacher-centered learning models that do not address student’s needs. The problem-based learning model enhances critical thinking, while the differentiated approach caters to individual students needs. Both methods are student-centered, aiding learners in understanding concepts and applying them in real life. Employing a quantitative ex post facto design, data were collected through questionnaires distributed to students. The variables studied include natural and social science learning outcomes (Y), problem-based learning models (X1), and differentiated approaches (X2). Data were tested for normality, linearity, multicollinearity, and heteroscedasticity before analysis. Hypothesis testing utilized simple correlation, multiple correlation, simple regression, multiple regression, determination tests, and F-tests. Results indicated that the problem-based learning model influenced learning outcomes by 4% (R square = 0.040), while the differentiated approach contributed 3.7% (R square = 0.037). combined, these approaches had a joint influence of 6.3% (R square = 0.063), positively affecting students learning outcomes in grade V at SD Mahesa Jenar Cluster, Ambarawa District, Semarang Regency.